Reaching the poor with health, nutrition, and population services : what works, what doesn't, and why - Gwatkin, Davidson R.; Wagstaff, Adam.; Yazbeck, Abdo. (Washington, DC : The World Bank, 2005)
This volume presents eleven case studies that document how well or how poorly health, nutrition, and population programmes have performed in reaching disadvantaged groups.
Includes bibliographical references and index.
osc 5/9/16, ijb 21/02/2019
Loans
Keywords: Poor---Medical care---Cross cultural studies; Poor---Nutrition; Health services accessibility; Health services